Pengaruh Kompetensi Pegawai terhadap Kinerja Pegawai melalui Motivasi sebagai Variabel Mediasi: Studi pada Kantor Badan Kepegawaian dan Pengembangan Sumber Daya Manusia (BKPSDM) Kabupaten Pamekasan - Chamariyah Chamariyah; Woro Utari; Fitriyah Rosdianingsih (Universitas 45 Surabaya, 2024)
Fitrih Rosdianingsih, 2024. The Influence of Employee Competence on Employee Performance Through Motivation as a Mediating Variable (Study at the Office of the Human Resources Development and Personnel Agency (BKPSDM) of Pamekasan Regency), Postgraduate Program, Wijaya Putra University. The type of research is explanatory, the research approach used is quantitative, the research sample is 42 respondents. Data analysis uses SPSS and PLS analysis. The objectives of this study are: 1) To test and analyze the influence of competence on the performance of employees of the Regional Revenue and Financial Management Agency (BPKPD) of Pamekasan Regency; 2) To test and analyze the influence of competence on the motivation of employees of the Regional Revenue and Financial Management Agency (BPKPD) of Pamekasan Regency; 3) To test and analyze the influence of motivation on the performance of employees of the Regional Revenue and Financial Management Agency (BPKPD) of Pamekasan Regency; 4) To test and analyze the influence of employee competence on the performance of employees of the Regional Revenue and Financial Management Agency (BPKPD) of Pamekasan Regency mediated by motivation. The results of the study indicate that: 1) Employee competence has a significant effect on the performance of employees of the Financial Management and Regional Revenue Agency (BPKPD) of Pamekasan Regency with an original sample value of 0.228; 2) Employee competence has a significant effect on the motivation of the Financial Management and Regional Revenue Agency (BPKPD) of Pamekasan Regency with an original sample value of 0.376; 3) Motivation has a significant effect on the performance of employees of the Financial Management and Regional Revenue Agency (BPKPD) of Pamekasan Regency with an original sample value of 0.499; 4) Employee competence has a significant effect on the performance of employees of the Financial Management and Regional Revenue Agency (BPKPD) of Pamekasan Regency mediated by motivation with an original sample value of 0.188.